Determination of Malaysian consumer intention toward purchasing Takaful scheme for mental health disorders - Khairi, Khairil Faizal; Laili, Nur Hidayah; Kamarubahrin, Aimi Fadzirul (Jurnal Ekonomi & Keuangan Islam, 2020)
Purpose – The purpose of this paper is to determine the factors influencing Malaysian consumer toward intention to purchase Takaful scheme for mental health disorders. Design/methodology – This paper adopts a quantitative approach by using an extended Theory of Reasoned Action (TRA) model. A pilot study with the total of 60 questionnaires were obtained from online survey to examine the significance relationship using multiple regression analysis. Findings – The result from this study portrays that subjective norm are strong predictors of a Malaysian consumer intention to purchase Takaful scheme for mental health disorders. Moreover, factors such as awareness, perception and attitude have positive and significant impacts on consumer intention to purchase takaful scheme for mental health disorders in Malaysia. Research limitation – There are some constraints. First, it focuses only on the actions of Malaysian consumers against a takaful scheme for mental health disorders; thus, the findings cannot be generalized to other takaful schemes. Therefore, more studies in other takaful settings, such as general takaful, need to begin. Second, this study considered only four factors were awareness, perception, attitude and subjective norm, and the factors selected might not cover all the factors which may have an effect on Malaysia’s intentions toward takaful mental health disorders scheme. Originality - This study not only helps takaful operators design, develop and promote better approved takaful products and services, but also offers a new insight into how these products and services can be marketed to these particular consumers. Previous empirical studies that employed TRA focused on various types of variables, such as attitude and subjective norm, especially in the financial service environment. This research thus adds to the body of information by analysing the relative value of the goal affecting it.